Natural frequency optimization of vehicle components using the interior search algorithm - Yıldız, Betül Sultan (Carl Hanser Verlag, 2017)
In the automotive industry, optimum design must be achieved to compete with strong competitors. Thus, it is aimed to reduce the cost, increase the quality and reduce the total production time. In this study, the natural frequency optimization of a vehicle sliding door linkage used to open and close the sliding doors on vehicles was made. In the optimization study for determining the optimum design model of the vehicle sliding door linkage, natural frequency was increased by 22.8 % using internal search algorithm.
Keywords: Optimum design; interior search; vehicle sliding door linkage